Chemotropism Assays for Plant Symbiosis and Mycoparasitism Related Compound Screening in Trichoderma atroviride - Moreno-Ruiz, Dubraska; Lichius, Alexander; Turrà, David; Di Pietro, Antonio; Zeilinger, Susanne (Frontiers in Microbiology, 2020)
Trichoderma atroviride is a mycoparasitic fungus used as biological control agent to protect plants against fungal pathogens. Successful biocontrol is based on the perception of signals derived from both the plant symbiont and the fungal prey. Here we applied three different chemotropic assays to study the chemosensing capacity of T. atroviride towards compounds known or suspected to play a role in the mycoparasite/plant or host/prey fungal interactions and to cover the complete spectrum of T. atroviride developmental stages. Purified compounds, including nutrients, the fungal secondary metabolite 6-amyl-α-pyrone (6-pentyl--pyrone, 6PP) and the plant oxylipin 13-(s)-HODE, as well as culture supernatants derived from fungal preys, including Rhizoctonia solani, Botrytis cinerea and Fusarium oxysporum, were used to evaluate chemotropic responses of conidial germlings, microcolonies and fully differentiated mycelia. Our results show that germlings respond preferentially to compounds secreted by plant roots and T. atroviride itself than to compounds secreted by prey fungi. With the progression of colony development, host plant cues and self-generated signalling compounds remained the strongest chemoattractants. Nevertheless, mature hyphae responded differentially to certain prey-derived signals. Depending on the fungal prey species, chemotropic responses resulted in either increased or decreased directional colony extension and hyphal density at the colony periphery closest to the test compound source. Together these findings suggest that chemotropic sensing during germling development is focused on plant association and colony network formation, while fungal prey recognition develops later in mature hyphae of fully differentiated mycelium. Furthermore, the morphological alterations of T. atroviride in response to plant host and fungal prey compounds suggest the presence of both positive and negative chemotropism. The presented assays will be useful for screening of candidate compounds, and for evaluating their impact on the developmental spectrum of T. atroviride and other related species alike. Conidial germlings proved particularly useful for simple and rapid compound screening, whereas more elaborate microscopic analysis of microcolonies and fully differentiated mycelia was essential to understand process-specific responses, such as plant symbiosis and biocontrol.